Efektivitas Kualitas Sumber Daya Manusia Melalui Peran dari BUMDes Dalam Peningkatan Pendapatan di Desa Wonotunggal Berbasis Pada Potensi Lokal - Ika Yunita Ratnasari; Yuyun Safitri Cahyani Arumsari; Ratih Pratiwi (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2022)
This study aims to determine the effect of the quality of human resources in the development of BUMDes in Wonotunggal Village. BUMDes in this area are very interesting to discuss because the MSME products that are sold are diverse, so these BUMDes produce local products that can become the hallmark of the village. This type of research uses a qualitative descriptive approach. Meanwhile, the data collection techniques used were interviews and observations. One of the advantages of using this method is that you can get to know the research environment better and can see firsthand the process and its constraints. The result of this study is that the quality of human resources in Wonotunggal Village does not only improve the quality of human resources who are members of BUMDes. However, at the same time developing and training the ability to advance the region by establishing MSMEs through BUMDes that utilize local potential. With the existence of BUMDes, it really helps the community to manage MSMEs in improving the family economy. Because the obstacles and constraints faced by BUMDes have begun to be overcome, BUMDes has a strategy to increase sales attractiveness, namely by utilizing social media to expand its marketing. BUMDes also take advantage of their foreign language skills as a characteristic of Wonotunggal Village, Kedungmalang District, Batang Regency.